Incidence and mortality of laryngeal cancer in China, 2015 - He, Yutong (Chin J Cancer Res, 2020)
OBJECTIVE: Using data from cancer registries to estimate laryngeal cancer incidence and mortality in China, 2015. METHODS: Data submitted from 501 cancer registries were checked and evaluated according to the criteria of data quality control and 368 registries’ data were qualified for the final analysis. Data were stratified by area (urban/rural), sex, age group and combined with national population data to estimate laryngeal cancer incidence and mortality in China, 2015. China population census in 2000 and Segi’s population were used for age-standardized. RESULTS: The percentage of cases morphological verified (MV%) of laryngeal cancer was 74.18%. The percentage of death certificate-only cases (DCO%) was 2.10%. And the mortality to incidence (M/I) ratio was 0.55. About 25,300 new cases of laryngeal cancer were diagnosed in 2015 and 13,700 deaths were reported. The crude rate of laryngeal cancer was 1.84 per 100,000 (males and females were 3.20 and 0.42 per 100,000, respectively). Age-standardized incidence rates by Chinese standard population (ASIRC) and by world standard population (ASIRW) were 1.18 and 1.19 per 100,000, respectively. The cumulative incidence rate (0−74 years old) was 0.15%. The crude mortality rate was 1.00 per 100,000. Age-standardized mortality rates by Chinese standard population (ASMRC) and by world standard population (ASMRW) were 0.61 and 0.61 per 100,000, respectively, with the cumulative rate (0−74 years old) was 0.07%. Incidence and mortality of laryngeal cancer in males were higher than those in females. And the rates in urban areas were higher than those in rural areas. CONCLUSIONS: The incidence and mortality of laryngeal cancer in China were low. And the rates were significantly higher in males than in females. Risk factor control and targeted prevention should be strengthened.